3D Printable Dynamic Hydrogel: As Simple as it Gets!. Issue 21 (4th August 2022) - Díaz, Aitor; Herrada‐Manchón, Helena; Nunes, Juliana; Lopez, Aitziber; Díaz, Natividad; Grande, Hans‐Jürgen; Loinaz, Iraida; Fernández, Manuel Alejandro; Dupin, Damien
Abstract: 3D printing technology offers a vast range of applications for tissue engineering applications. Over the past decade a vast range of new equipment has been developed; while, 3D printable biomaterials, especially hydrogels, are investigated to fit the printability requirements. The current candidates for bioprinting often require post‐printing cross‐linking to maintain their shape. On the other hand, dynamic hydrogels are considered as the most promising candidate for this application with their extrudability and self‐healing properties. However, it proves to be very difficult to match the required rheological in a simple material. Here, this study presents for the first time the simplest formulation of a dynamic hydrogel based on thiol‐functionalized hyaluronic acid formulated with gold ions that fulfill all the requirements to be printed without the use of external stimuli, as judged by the rheological studies. The printability is also demonstrated with a 3D printer allowing for the printing of the dynamic hydrogel as it is, achieving 3D construct with a relatively good precision and up to 24 layers, corresponding to 10 mm high. This material is the simplest 3D printable hydrogel and its mixture with cells and biological compounds is expected to open a new era in 3D bioprinting. Abstract : For the first time, a dynamic hydrogel based on hyaluronic acid can be printed without any additional post‐processing. Thanks to the permanent exchange between gold‐thiolate species and disulfide, the material matches the perfect rheological properties for its printability, that is, low viscosity, injectability and self‐healing properties, achieving large object with more than 20 layers.